A comparative study of two landslide events at Sultan Ahmad Shah mosque, Jengka, Pahang - Alias, Rohaya; Bachok, Mohd Fairuz (2009)
Landslide has become a very serious problem in Malaysia lately. Landslides can be caused by a number of factors including slope geometry, soil types and properties, rainfall effects, infiltration, erosion and drainage system. In order to determine the landslide risk based on the soil physical properties, ROM scale method can be used In this study, the slope at Sultan Ahmad Shah Mosque, Jengka, Pahang which consists of failure zones and un-failed zones next to the failure zones was selected to asses the relationship between the soil physical properties in term of particle size distribution and the slope failure using ROM scale method. Sieve analysis and hydrometer tests were conducted to determine the ROM values. From the research finding, all the soil samples taken from the failure zones were in the critical risk category and the soil samples taken from un-failed zones were in the moderate and high risk category.